Impact of field fertility clinic on dairy production in peri urban areas of Chittagong District - Islam, MS; Sikder, MSI; Hossain, MM; Akteruzzaman, M; Shamsuddin, M (Bangladesh Journal of Animal Science, 2012)
The study was undertaken to compare the relative profitability of dairy farming under Field Fertility Clinic (FFC) member and non-members. A total of 130 samples were selected randomly of which 100 were members and 30 were non-members. Total cost of raising dairy cow was estimated at Tk. 142.04 and Tk. 158.21/day for member and non-member farmers. Feed cost constituted about 71.64 per cent and 69.94 per cent of total cost for member and non-member farmers respectively. Concentrate occupied the largest share out of total feed cost. In case of member, net return per day per cow was Tk. 96.02 while in the case of non-member it was Tk. 65.94. Return from per dairy cow of the members was higher by Tk. 30.08 than the non-members. The average milk yield was 6.06 liters and 5.81 liters respectively for member and non-member farmers. Cobb-Douglas production function analysis was done to determine the effects of variables inputs such as concentrate feed, paddy straw, green grass, human labour, veterinary cost and FFC intervention on milk yield. The finding showed that all of the selected variables except paddy straw had significant impact on milk yield. Key words: Field fertility clinic; Milk yield; Cobb-Douglas production function; Net return DOI: http://dx.doi.org/10.3329/bjas.v39i1-2.9694 Bang. J. Anim. Sci. 2010, 39(1&2): 183-190